Coherent backscattering by large ice crystals of irregular shapes in cirrus clouds - Kustova, Natalia V.; Konoshonkin, Alexander V.; Shishko, Viсtor A.; Timofeev, Dmitriy N.; Borovoi, Anatoli G.; Wang, Zhenzhu (Atmosphere)
All elements of the scattering matrix have been numerically studied for particles of irregular shapes whose size is much larger than incident wavelength. The calculations are performed in the physical optics approximation for a particle size of 20 mu m at a wavelength of 0.532 mu m. Here the scattered intensity reveals the backscattering coherent peak. It is shown that the polarization elements of the matrix reveal the surges within the backscattering peak. The angular width of the surges does not practically depend on particle shape, but depends on the particle size. It is shown that these surges are created by interference between the conjugate scattered waves propagating in the inverse directions. The results obtained are of interest for interpretation of lidar measurements in cirrus clouds.